2019
DOI: 10.2337/dc19-0315
|View full text |Cite
|
Sign up to set email alerts
|

Age, HLA, and Sex Define a Marked Risk of Organ-Specific Autoimmunity in First-Degree Relatives of Patients With Type 1 Diabetes

Abstract: Autoimmune diseases can be diagnosed early through the detection of autoantibodies. The aim of this study was to determine the risk of organ-specific autoimmunity in individuals with a family history of type 1 diabetes. RESEARCH DESIGN AND METHODS The study cohort included 2,441 first-degree relatives of patients with type 1 diabetes who were prospectively followed from birth to a maximum of 29.4 years (median 13.2 years). All were tested regularly for the development of autoantibodies associated with type 1 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
0
17
0
2
Order By: Relevance
“…Serum aTPO and aTg are relatively common in subjects suffering from other endocrine conditions, such as T1D and AD, and in systemic autoimmunity (2,3,39,40). A prospective study in close relatives of patients with T1D revealed that by 20 years of age the overall risk of developing aTPO exceeds 10% (40). In our analysis, aTPO were the only autoantibodies, which displayed gender difference, with more than twice increased preponderance in females.…”
Section: Figurementioning
confidence: 49%
See 1 more Smart Citation
“…Serum aTPO and aTg are relatively common in subjects suffering from other endocrine conditions, such as T1D and AD, and in systemic autoimmunity (2,3,39,40). A prospective study in close relatives of patients with T1D revealed that by 20 years of age the overall risk of developing aTPO exceeds 10% (40). In our analysis, aTPO were the only autoantibodies, which displayed gender difference, with more than twice increased preponderance in females.…”
Section: Figurementioning
confidence: 49%
“…Their frequencies in iodine-sufficient populations range between 5 and 18% and tend to rise in elderly women (17). Serum aTPO and aTg are relatively common in subjects suffering from other endocrine conditions, such as T1D and AD, and in systemic autoimmunity (2,3,39,40). A prospective study in close relatives of patients with T1D revealed that by 20 years of age the overall risk of developing aTPO exceeds 10% (40).…”
Section: Figurementioning
confidence: 99%
“…2. First-degree relatives had an increased risk of developing both the disorders compared to the general population [5,13].…”
Section: Diabetes and CDmentioning
confidence: 87%
“…These studies have revealed that over 90% of children with T1D have autoantibodies to at least one islet-specific autoantibody at diagnosis and that these can appear years before clinical diagnosis of T1D. The first autoantibody to appear is against insulin, with a peak incidence around age 12 months [14,15]. Up to 90% of children with a single type of islet-specific autoantibody do not progress to T1D, but seroconversion to the presence of two or more autoantibodies (which occurs at a median age of 2.1 yrs) comes with an 84% risk of clinical T1D by the age of 18 [16].…”
Section: Autoantibodies As Biomarkers Of Early Diseasementioning
confidence: 99%